Ensino agrícola, trabalho e modernização no campo : a origem da Escola Superior de Agricultura e Veterinária do Estado de Minas Gerais (1920-1929) - Silva, Fabricio Valentim da (2007)
This search is located in the Education Institutions History field and it aims to interpret the Agricultural and Veterinary Superior School of Minas Gerais (ESAV) construction project known by Viçosa School in the period between 1920 and 1929. The beginning of this educational institution and the agriculture conservator modernization are subjects of this search. The analyses are based on many primary documents such as letters, book notes, interior policies, teaching methods, state laws, graduation books and pictures. Those sources are archived in the Historic Archive from the Universidade Federal de Viçosa (UFV). The sources indicate that the ESAV construction is based on a project for rural development and diversification in Minas Gerais state, and it was made to enhance agricultural rationalization and modernization through the invention of an ideal kind of farmer: the modern farmer. This recovering project for Minas Gerais economy was drowned by the government and rural elites at Minas Gerais Rural Economic Forum that took place in Belo Horizonte MG, from 13th to 19th of may, in the year 1903.This meeting conferred to the state agricultural school the responsibility to form, to qualify and to organize rural workers, so all the technical innovations about crop working and animal handling could be transmitted to all social groups of rural workers at that time. This process takes part on the illuminist thoughts that transfer to the technical knowledge the responsibility to endorse progress and civilization in the country. It can be highlighted on this search two different periodsthat marked the settings and evolution of agricultural teaching in Minas Gerais. The first period was characterized by state politics materialization for the sector with emphasis on basical education for agricultural work. This education, based on thoughts of positivism and that marked the historical period post-slavery promoted the qualification of elementary Agricultural instruction in two levels: the professional teaching in schools and the practical teaching for adults laborers. The positivist man João Pinheiro was the main sponsor for this first stage. On the second stage of evolution the main focus was to renew the country, on technical sociologic and cultural terms, seeing as the strategies employed to reach production development and diversification searched by privileged groups in Minas Gerais at that meeting in 1903 was reshaped on President Arthur Bernardes administration (1918-1922) with the beginning of Escola de Viçosa, through the law #761 in 09/06/1920. This way, it has started the base for an effective modernization for Minas Gerais agriculture. In order t do it, president Arthur Bernardes reached the north American agricultural schooling model, the land Grant Colleges, the necessary political-pedagogical project to reach the desired aim. Persuaded by the political scientist Peter Henry Rolfs who was the main technical manager from ESAV, the school of Viçosa was shaped with the same features of an American agricultural college. In this educational project, the students from ESAV were the main diffusers for the modern thoughts for labors and crop fields in Minas Gerais. In other words, they should be the intellectual leaders of field modernization. This was the main reason for those young people was receiving modern scientific and technical agricultural knowledge, related to thoughts and moral civic hygienic ideas and schooling for the kind of work needed by rural politicians and employers at that time.